1994
DOI: 10.1590/s0102-311x1994000400007
|View full text |Cite
|
Sign up to set email alerts
|

Inter-relações entre os ciclos de transmissão do Trypanosoma cruzi no município de Bambuí, Minas Gerais, Brasil

Abstract: . This study examines recent relationships between domestic and sylvatic transmission cycles of T. cruzi in the county of Bambuí, MG, Brazil. In the late l930s, Panstrongylus megistus was found in 75% of houses. Subsequently, Triatoma infestans became the predominant species, found in 20% of urban households and in more than 60% of periurban homes. With intense insecticide control campaigns between l956 and l969, T. infestans was eradicated from the county, transmission of Chagas' disease to man was interrupte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
7
0
6
Order By: Relevance
“…Although parasite isolation methods may select for certain strains and lineages of T. cruzi, no lineage selection was recorded among 145 isolates from opossums in spite of using different methods (Fernandes et al, 1991). Experimental infections of Didelphis opossums with TCII were considered less persistent than infections with TCI (Fernandes et al, 1994). In addition, mixed infections with different lineages and sublineages contradict the hypothesis of strict sublineage selection by the host.…”
Section: Discussionmentioning
confidence: 99%
“…Although parasite isolation methods may select for certain strains and lineages of T. cruzi, no lineage selection was recorded among 145 isolates from opossums in spite of using different methods (Fernandes et al, 1991). Experimental infections of Didelphis opossums with TCII were considered less persistent than infections with TCI (Fernandes et al, 1994). In addition, mixed infections with different lineages and sublineages contradict the hypothesis of strict sublineage selection by the host.…”
Section: Discussionmentioning
confidence: 99%
“…A third cycle associated with anthropic environments can occur in several places where domestic animals are kept in sheds near dwellings, called by some authors a peridomestic cycle [5]. However, the epidemiological scenario of Chagas disease is more complex because it can include overlapping cycles [6][10], intrusions of wild vectors into human dwellings [11], [12], colonization and re-infestation of new sylvatic vector species after spraying houses [4], [13][15], the regular intrusion of wild mammals inside houses [16], house infestation by two vector species [17], etc.…”
Section: Introductionmentioning
confidence: 99%
“…3). Although the opossums tested here were not infected, Fernandes et al (1991Fernandes et al ( , 1994 demonstrated that these reservoirs play an important role in the interaction of the parasite's domestic and sylvatic cycles in Bambuí.…”
mentioning
confidence: 66%
“…The reduction in triatomine colonies in households is attributed mainly to the extensive vector control program that has been established for decades in Bambuí. However, unlike T. infestans, which is restricted to the household environment in Brazil, P. megistus has a wide distribution in nature and frequently moves between natural ecotopes and dwellings (Dias 1982, Fernandes et al 1994). The low rates of re-infestation (10%) and domiciliary colonies (20%) observed in residences evaluated between [2004][2005][2006][2007][2008][2009] suggest that the sylvatic environment is the main source of household recolonisation.…”
mentioning
confidence: 99%